2003
DOI: 10.1074/jbc.m208574200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of T4 Bacteriophage gp17 Terminase, a Large Subunit Multimer with Enhanced ATPase Activity

Abstract: Phage T4 terminase is a two-subunit enzyme that binds to the prohead portal protein and cuts and packages a headful of concatameric DNA. To characterize the T4 terminase large subunit, gp17 (70 kDa), gene 17 was cloned and expressed as a chitin-binding fusion protein.Following cleavage and release of gp17 from chitin, two additional column steps completed purification. The purification yielded (i) homogeneous soluble gp17 highly active in in vitro DNA packaging (ϳ10% efficiency, >10 8 phage/ml of extract); (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
88
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 33 publications
7
88
1
Order By: Relevance
“…S6). This alternative model may not necessarily be incompatible with previous data suggesting interactions between portals and terminase large subunits, because: (i) the terminase large subunit gp17 in T4 showed a multidomain architecture with extended linker regions among domains (7) which can potentially allow conformational change needed to reach the portal, and (ii) terminase small subunits stimulate the ATPase activity of large subunits, an activity required for DNA-packaging, as shown in phages T4 (34,35), SPP1 (36) and lambda (37), and this stimulation may result from conformational change of large subunits induced by binding of small subunits (38). A feature of this alternative model is that both terminase subunits participate in molecular interactions with the portal.…”
Section: Discussioncontrasting
confidence: 41%
“…S6). This alternative model may not necessarily be incompatible with previous data suggesting interactions between portals and terminase large subunits, because: (i) the terminase large subunit gp17 in T4 showed a multidomain architecture with extended linker regions among domains (7) which can potentially allow conformational change needed to reach the portal, and (ii) terminase small subunits stimulate the ATPase activity of large subunits, an activity required for DNA-packaging, as shown in phages T4 (34,35), SPP1 (36) and lambda (37), and this stimulation may result from conformational change of large subunits induced by binding of small subunits (38). A feature of this alternative model is that both terminase subunits participate in molecular interactions with the portal.…”
Section: Discussioncontrasting
confidence: 41%
“…Because a number of components constitute the packaging machine, and several ATPase sites have been identified (10,(21)(22)(23)39), the ATPase that powers DNA translocation remained uncertain. We have earlier demonstrated that the T4 large terminase protein gp17 exhibits ATPase and in vitro DNA packaging activities that are stimulated 50 -100-fold by the small terminase protein gp16 (11)(12)(13)40). Sequence alignments mapped a key ATPase in the N-terminal half of gp17 (10,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetics and biochemical evidence implicate this ATPase in DNA packaging. The evidence includes the following: (i) the T4 gp17 alone exhibits ATPase and in vitro DNA packaging activities (11,12); (ii) both the activities are stimulated 50 -100-fold by the small terminase protein gp16 (12,13); (iii) the N-terminal Walker A motif, 161 SRQLGKT 167 , is critical for function and any substitution in the conserved residues results in a loss of stimulated ATPase and in vitro DNA packaging activities (14); and (iv) a critical catalytic carboxylate, Glu 256 , which is involved in the cleavage of the ␤,␥-phosphoanhydride bond of ATP (15), has been identified.…”
mentioning
confidence: 99%
“…The ac and acq gp 17 genes were cloned as the wt gp 17 gene in pTYB2 plasmids and were expressed in BL21 (DE3) pLysS, successfully making the gp17-intein/chitinbinding domain fusion (27). Full-length active ac and acq gp17 was purified based on the Impact system of cloning (New England Biolabs, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…To make sure the sample was equilibrated-that is, that it only gave one band in electrophoresis-the samples were always run on 1.5% (wt/vol) agarose and at a 100 V constant field electrophoresis. Western blotting was carried out using a gp17 antiserum as previously described (27) after running the samples on 5% native PAGE gel under cold conditions.…”
Section: Methodsmentioning
confidence: 99%